What is Halal Restaurant? A Research Map based on Scopus Database - Rahayu, Solihah Sari; Nong, Nor Faridah Mat (Halal Tourism and Pilgrimage, 2024)
This study aims to see the development of research on the topic of "Halal Restaurant" and research plans that can be done based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Halal Restaurant" which comes from the Scopus database with a total of 123 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the blibliometric map of "Halal Restaurant" research development in the world. The results of the study found that there are 5 clusters with the most used words are: market, tourist, halal tourism, intention, relationship, effect, halal product, process, practice, information, and Muslim tourist. Then, the topics of research lines related to Halal Restaurant are (1) Demand for Halal Restaurants, (2) Behavioral Intention Toward Halal-Certified Restaurants, (3) Halal Restaurant Trends in Global Markets, (4) Customer Satisfaction and Trust in Halal Restaurants, and (5) Halal Tourism and Halal Restaurant.